Morphology of Co–Cr–Mo dental alloy surfaces polished by three different mechanical procedures. Issue 9 (17th July 2015) - Ţălu, Ştefan; Stach, Sebastian; Klaić, Boris; Mišić, Tea; Malina, Jadranka; Čelebić, Asja
ABSTRACT The present study aims at characterizing the three‐dimensional (3‐D) morphology of a Co–Cr–Mo dental alloy surface as a result of three different procedures used for polishing it. The sample surface morphology of the sampled surface was examined employing atomic force microscopy (AFM), statistical surface roughness parameters, and fractal analysis. An extra‐hard dental alloy of cobalt–chromium–molybdenum (Co–Cr–Mo) (Wironit®, from BEGO, Bremen, Germany) was prepared and moulded. Different polishing treatments were carried out on three groups of six samples each—a total of 18 samples. The first group contained six electropolished (EP) samples. The second group containing six samples went through a mechanical polishing process employing green rubber discs and a high shine polishing paste applied by a rotating black brush (BB). The third group comprising six samples as well went through a mechanical polishing process by means of green rubber discs, high shine polishing paste, and a rotating deer leather brush (DL). Fractal analysis on the basis of a computational algorithm applied to the AFM data was employed for the 3‐D quantitative characterization of the morphology of the sampled surfaces. The fractal dimension D (average ± standard deviation) of 3‐D surfaces for BB samples (2.19 ± 0.07) is lower than that of the DL samples (2.24 ± 0.08), which is still lower than that of the EP samples (2.27 ± 0.09). The results indicated the BB samples as presenting the lowest values of statistical surface roughness parameters, thus the best surface finish, while the EP samples yielded the highest values. Microsc. Res. Tech. 78:831–839, 2015. © 2015 Wiley Periodicals, Inc.